Climate Risk Management for Agricultural Extension (CRMAE) Training-of- Trainers for MASAE Bureau for Professional Agricultural Training - Hansen, James; Diop, Mbaye; Trzaska, Sylwia; Cisse, Serigne; Worou, Nadine; Wane, Abdrahmane (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report summarizes the Climate Risk Management for Agricultural Extension (CRMAE) Training-of-Trainers (ToT) workshop held from 29 September to 4 October 2024 in Diamniandio, Senegal, organized by the AICCRA project in collaboration with MASAE and BFPA. The training aimed to strengthen the capacity of agricultural extension and advisory service (EAS) providers by equipping them with climate-smart tools and knowledge to support farmers in managing climate risks. The curriculum, developed through a series of consultations, focused on climate information services, climate-sensitive agricultural decisions, and strategies for delivering climate services. Participants, including professionals from agricultural training centers across Senegal, learned to apply climate data to improve risk management and decision-making for farmers. The workshop also focused on integrating the CRMAE content into BFPA’s training programs. This initiative is part of broader efforts to enhance the resilience of Senegal's agricultural sector to climate change by integrating climate knowledge into vocational and continuing education.